2002
DOI: 10.1097/01.lab.0000041709.42598.4a
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Calnexin Reflects Paneth Cell Differentiation and Function

Abstract: SUMMARY:It has been suggested that the behavior and function of Paneth cells in metaplasia are different from those found in normal intestinal mucosa. In this study, we investigated whether calnexin, a protein involved in secretory pathways, might be associated with differentiation and function of Paneth cells in normal small intestine, in complete intestinal metaplasia of the stomach, and in Paneth cell-rich adenomas. Differentiation and function of Paneth cells was monitored by Ki67, lysozyme, and morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Esophagus Conventional H&E staining Chen et al, 2015 H&E, light microscopy and electron microscopy Schreiber et al, 1978 H&E, periodic acid-Schiff/Alcian blue Takubo et al, 1995 H&E, Lendrum's Phyloxine-tartrazine stain Thompson et al, 1983 Stomach Periodic acid-Schiff/Alcian blue at pH 2.5 Abraham et al, 2003 H&E, Masson's Trichome, Lendrum's Phyloxine-tartrazine, Periodic acid-Schiff/Alcian blue at pH 2.5 and colloidal iron pH 1.9 staining Albedi et al, 1984 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5, immunostaining for lysozyme Deveci and Deveci, 2004 Immunostaining for lysozyme Gassler et al, 2002 Conventional H&E staining Inada et al, 1997 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5 and Electron microscopy Matsubara, 1977 Immunoelectron microscopy for lysozyme Ohtani and Sasano, 1988 Immunostaining for HD5 and HD6 Ostaff et al, 2015 Conventional H&E staining Rubio et al, 1987 Lysozyme immunostaining Rubio, 2012 Gallbladder Conventional H&E staining Albores-Saavedra et al, 1986 Conventional H&E staining Bae et al, 2002 Electron microscopy, H&E, Periodic acid-Schiff Laitio and Nevalainen, 1975 Conventional H&E staining Sakaki et al, 2000 Ovary Conventional H&E staining Alrajban et al, 2018 Conventional H&E staining Niemiec et al, 1989 Prostate Conventional H&E staining, immunostaining for lysozyme Frydman et al, 1992 Conventional H&E staining Adlakha and Bostwick, 1994 (Shen et al, 2005). Additionally, Paneth-like cells were reported in gastric adenomas and carcinomas (Heitz and Wegmann, 1980;Ito et al, 1986;Caruso et al, 1989;Rubio, 1989).…”
Section: Methods Of Identification Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophagus Conventional H&E staining Chen et al, 2015 H&E, light microscopy and electron microscopy Schreiber et al, 1978 H&E, periodic acid-Schiff/Alcian blue Takubo et al, 1995 H&E, Lendrum's Phyloxine-tartrazine stain Thompson et al, 1983 Stomach Periodic acid-Schiff/Alcian blue at pH 2.5 Abraham et al, 2003 H&E, Masson's Trichome, Lendrum's Phyloxine-tartrazine, Periodic acid-Schiff/Alcian blue at pH 2.5 and colloidal iron pH 1.9 staining Albedi et al, 1984 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5, immunostaining for lysozyme Deveci and Deveci, 2004 Immunostaining for lysozyme Gassler et al, 2002 Conventional H&E staining Inada et al, 1997 H&E, Periodic acid-Schiff/Alcian blue at pH 2.5 and Electron microscopy Matsubara, 1977 Immunoelectron microscopy for lysozyme Ohtani and Sasano, 1988 Immunostaining for HD5 and HD6 Ostaff et al, 2015 Conventional H&E staining Rubio et al, 1987 Lysozyme immunostaining Rubio, 2012 Gallbladder Conventional H&E staining Albores-Saavedra et al, 1986 Conventional H&E staining Bae et al, 2002 Electron microscopy, H&E, Periodic acid-Schiff Laitio and Nevalainen, 1975 Conventional H&E staining Sakaki et al, 2000 Ovary Conventional H&E staining Alrajban et al, 2018 Conventional H&E staining Niemiec et al, 1989 Prostate Conventional H&E staining, immunostaining for lysozyme Frydman et al, 1992 Conventional H&E staining Adlakha and Bostwick, 1994 (Shen et al, 2005). Additionally, Paneth-like cells were reported in gastric adenomas and carcinomas (Heitz and Wegmann, 1980;Ito et al, 1986;Caruso et al, 1989;Rubio, 1989).…”
Section: Methods Of Identification Referencesmentioning
confidence: 99%
“…This represented one of the earliest attempts to distinguish intestinal resident cells vs. metaplastic Paneth cells. Gassler et al (2002) later reported that the expression of calnexin was inversely related to secretory lysozyme in Paneth cells of normal intestinal mucosa but became directly correlated to lysozyme in metaplastic Paneth cells in gastric mucosa. They further identified the expression of proliferative marker Ki67 in metaplastic Paneth cells but not in Paneth cells of normal small intestines.…”
Section: Methods Of Identification Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gassler et al (2002) reported Paneth cells of IMs in the gastric mucosa and Paneth cell-rich adenoma express the proliferation marker Ki67, a phenomenon that was never observed in Paneth cells of normal small intestine. Moreover, Wong et al (2000) emphasized that numerous Paneth cells and goblet cells in areas of intestinal metaplasia were in cell cycle; however, the endocrine cells were non-proliferative.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium binding protein in the endoplasmic reticulum, cnx, is a molecular chaperone that helps with the correct folding of mhc class i molecules to form a functional dimer 35,36 . Reduced expression or absence of cnx may therefore lead to downregulation of mhc-i expression 37,38 .…”
Section: Discussionmentioning
confidence: 99%